Glycemic Control Regimens in the Prevention of Surgical Site Infections: A Meta-Analysis of Randomized Clinical Trials - Lai, Jing; Li, Qihong; He, Ying; Zou, Shiyue; Bai, Xiaodong; Rastogi, Sanjay (Frontiers in Surgery, 2022)
Background: Increased risk of surgical site infections (SSI) caused by hyperglycaemia makes it necessary to follow perioperative glucose lowering strategies to reduce post-operative complications. A meta-analysis was conducted to understand the efficacy of intensive versus conventional blood glucose lowering regimens on SSI and hypoglycaemia incidence from various RCTs. Materials and Methods: A systematic literature review was conducted using MEDLINE and Central databases for RCTs that involved intensive (lower blood glucose target levels) versus conventional (higher blood glucose target levels) strategies in patients undergoing various types of surgeries. The primary outcome was surgical site infection (SSI) or post-operative wound infections. Hypoglycaemia and mortality outcomes were also studied. A random-effects model was used to calculate the pooled risk ratio and subgroups analyses was performed. Results: A total of 29 RCTs were included in the meta-analysis with information from 14,126 patients. A reduction in overall SSI incidence was found (RR 0.63, 0.50-0.80, P=0.0002, I2=56%). Subgroup analyses showed that intensive insulin regimens decreased the risk of SSI in diabetic patients, in cardiac and abdominal surgical procedures, and during the intraoperative and postoperative phases of surgery. However, the risk of hypoglycaemia and mortality was increased in the intensive group compared to the conventional group. Conclusion: The results of the meta-analysis provide support for the use of intensive insulin regimens during perioperative phase for decreasing SSI incidence in certain patient populations and surgical categories.